The THE ANALYSIS OF SCHOOL CULTURE, PRINCIPAL LEADERSHIP, AND EMOTIONAL INTELLIGENCE TOWARDS SATISFACTION AND OUTCOME OF TEACHER PERFORMANCE IN ALL OF PUBLIC HIGH SCHOOLS IN SAMALANGA SUB-DISTRICT, BIREUEN - Win, admin; Raihan, Nazaruddin (LPPM-UNIKI, 2020)
This study aims to analyse the influence of; 1) School culture on jobsatisfaction 2) Principal leadership on job satisfaction, 3). Emotionalintelligence on job satisfaction, and 4) Job satisfaction on teacher performance.The sample of this research is 50 teachers in Public High School in SamalangaSub-District, Bireuen Regency. The method is descriptive and verification,specifically by using path analysis approach. The results show a significanteffect of 4 variables used; 1). 17.74% School Culture on Job Satisfaction, 2)18.09% Principal Leadership on Job Satisfaction 3). 15.28% Emotionalintelligence on job satisfaction 4). Job satisfaction affects teacher performanceby 30.58%.